Analisis Motivasi Intrinsik dan Ekstrinsik dalam Meningkatkan Kinerja Perangkat Desa Lintongnihuta - Jayanti, Mesdiana Titi; Wira, Teguh Satya (Program Pascasarjana STIE Amkop Makassar, 2024)
Motivation is a necessity, whether consciously or not, in moving Human Resources, so motivation is needed so that employees can work optimally. Motivation is not only limited to material but other types of motivation must be stimulated so that they can develop naturally, every human being has motivation in themselves in working because every human being has desires and hopes in their lives, this is called intrinsic motivation. While extrinsic motivation is motivation that comes from outside the human self. This is also something that must be considered, promotion, mutation, is one part of this motivation, apart from bonuses, incentives and salaries. Both of these motivations, both internal and external to humans, must be aligned which will ultimately improve employee performance. Employee performance is a measure of the extent to which employees succeed in achieving company goals and standards set by the company, employee performance can also be interpreted as employee achievement in carrying out main tasks and functions and responsibilities for the work done. Or in other words, employee performance is the ability, skills and work results shown by an employee in carrying out tasks and responsibilities in the workplace. Employee performance can be measured by achieving predetermined targets, work productivity, quality of work results and quality of work in a team. This research was conducted by the author, namely the Lintongnihuta Village Office in Samosir Regency, North Sumatra.